2016
DOI: 10.7324/japs.2016.60525
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antioxidant and anti-inflammatory properties of selected Moroccan medicinal plants

Abstract: The aim of the present study was to examine the antioxidant and anti-inflammatory activities of three Moroccan ethno medicinally important plants. The antioxidant activity was performed using β-Carotene bleaching assay, DPPH, ABTS and Ferric reducing assays. In vitro anti-inflammatory assays was also studied through the evaluation of membrane stabilization potential and inhibition of protein denaturation. Results revealed that Lawsonia inermis L leaves extract had significantly higher phenolics-content (5.23 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…HRBC stabilization evaluation of the leaf extracts was carried out according to the Gandhisan et al, (1991), Murugan and Parimelazhagan, (2014) and Bouhlali et al (2016) methods with some modifications. Whole human blood was collected from volunteers (who had not taken any NSAIDS for 2 weeks prior to the experiment) and mixed with equal volume of Alsever's solution which was prepared by dissolving 2% dextrose, 0.80% sodium citrate, 0.05% citric acid and 0.42% sodium chloride in sterilized double distilled water.…”
Section: Human Red Blood Cells Stabilization Methods (Hrbc):-mentioning
confidence: 99%
See 2 more Smart Citations
“…HRBC stabilization evaluation of the leaf extracts was carried out according to the Gandhisan et al, (1991), Murugan and Parimelazhagan, (2014) and Bouhlali et al (2016) methods with some modifications. Whole human blood was collected from volunteers (who had not taken any NSAIDS for 2 weeks prior to the experiment) and mixed with equal volume of Alsever's solution which was prepared by dissolving 2% dextrose, 0.80% sodium citrate, 0.05% citric acid and 0.42% sodium chloride in sterilized double distilled water.…”
Section: Human Red Blood Cells Stabilization Methods (Hrbc):-mentioning
confidence: 99%
“…There reason why these assay methods selected was due to ethical challenges and the nonexistence of rationale to use animals for pharmacological research of new chemical compounds (Bouhlali et al 2016). …”
Section: Anti Inflammatory Activity:-mentioning
confidence: 99%
See 1 more Smart Citation
“…Quantification of phenols within the three extracts was executed using Folin–Ciocalteu's reagent, following the protocol reported by Bouhlali et al [ 17 ] whose principle relies on the decay of phosphomolybdic-phosphor tungstic acid caused by phenol compounds in an alkaline medium [ 18 ]. To proceed, 500 µ L of Folin–Ciocalteu's reagent diluted ten-fold in water was poured onto 100 µ L of a suitable diluted hydromethanolic plant extract and, then, 400 µ L of sodium carbonate solution (7.5% w/v).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Oteiza et al [28] have suggested that interactions of polyphenols at the surface of bilayers through hydrogen bonding can act to reduce the access of deleterious molecules (i.e., oxidants), therefore protecting the structure and function of membranes. Several reports have mentioned that plant flavonoids and polyphenols have anti-inflammatory characteristics [29].…”
Section: Membrane Stabilizing Potentialmentioning
confidence: 99%